Features of immune metabolism of lymphocytes in pancreatic lymph nodes during experimental steptozotocin-induced diabetes mellitus and after introduction of metformin - Putilin D.A.; Kamyshny A.M. (Морфологія, 2016)
Background. Metabolic changes in terms of developing diabetes, especially hyperglycemia, can directly affect immune metabolism of lymphocytes. Objective: The aim was to find out the level of mRNA gene expression of Glut1, mTOR and AMPK1α in pancreatic lymphatic nodes (PLN) in rats with experimental streptozotocin-induced diabetes mellitus (ESIDM) and after introduction of metformin. Methods. Glut1, mTOR and AMPK1α mRNA expression were analyzed by real-time reverse transcriptase-polymerase chain reaction. Total RNA was extracted from PLN tissue by Trizol RNA Prep 100 (Isogen, Russia), according to the manufacturer's instructions. RNA was re-suspended in RNase free water, quantified and subjected to RT-PCR reaction using RT-PCR kit; RT (Syntol, Russia). To determine the level of Glut1, mTOR and AMPK1α mRNA, RT-PCR was performed in real-time by thermal cycler CFX96 ™ Real-Time PCR Detection Systems (Bio-Rad Laboratories, Inc., USA). The relative level of gene expression were studied with rat reference genes GAPDH by the method ΔΔCt. Statistical analysis were conducted using available software «Bio-Rad SFX Manager 3.1» (Bio-Rad, USA). Results. It was established that hyperglycemia caused the transcript induction of genes of glucose transporter Glut1 (in 9,9-28,9 times, p<0,05) and protein kinase mTOR (in 5.3-3.3 times, p<0.05) in cells of PLN. Introduction of metformin to the diabetic rats resulted in an increased level of mRNA gene of AMPK1αby on 87% (p<0.05) on the 3rd week and 38 fold (p<0.05) on the 5th week of ESIDM development and inhibition of mTOR expression in PLN (in 3-14.7 times, p<0.05). Revealed increase of Glut1 and mTOR mRNA genes level in the PLN cells during diabetes can trigger their differentiation in effective pro-inflammatory subpopulation of Th1- and Th17-lymphocytes. Conclusion. Increased level of AMPK1α mRNA and inhibition of mTOR expression in PLN after metformin introduction to diabetic rats gives evidence about the possibility for correction of immune violations that develop during diabetes. Citation: Putilin DA, Kamyshny AM. Features of immune metabolism of lymphocytes in pancreatic lymph nodes during experimental steptozotocin-induced diabetes mellitus and after introduction of metformin. Morphologia. 2016;10(2):61-8. Ukrainian.